1987
DOI: 10.1029/ja092ia05p04525
|View full text |Cite
|
Sign up to set email alerts
|

Electron precipitation in the vicinity of a VLF transmitter

Abstract: Using high‐resolution pitch angle measurements made by a magnetic focusing electron spectrometer on the S3‐3 satellite, angular distributions of 235‐keV electrons precipitated in the slot region of the magnetosphere by a ground‐based VLF transmitter are compared with the pitch angle distributions that would be produced by various patterns of longitudinal interaction regions. The observed electrons are in the drift loss cone, necessitating the use of a trace‐back‐to‐longitude‐of‐origin technique coupled with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Considering that the frequencies of the transmitters are between 10 and 25 kHz and using Equation (18), it is shown that the energy of the precipitated particles is a few keV. The resonance condition for relativistic electrons with a local pitch angle a is given by (Koons et al, 1981;Vampola, 1987):…”
Section: Electron Precipitationmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that the frequencies of the transmitters are between 10 and 25 kHz and using Equation (18), it is shown that the energy of the precipitated particles is a few keV. The resonance condition for relativistic electrons with a local pitch angle a is given by (Koons et al, 1981;Vampola, 1987):…”
Section: Electron Precipitationmentioning
confidence: 99%
“…Their ionospheric perturbations have mainly been observed in-situ by satellites. It includes: triggering of new waves (Dowden et al, 1978;Bell et al, 1983;Titova et al, 1984;Bell, 1985;Groves et al, 1988;Bell andNgo, 1988, 1990;Sotnikov et al, 1991), ionospheric heating (Inan, 1990;Bell et al, 1991;Dowden and Adams, 1992;Inan et al, 1992;, wave-electron interactions (Inan et al, 1978;Inan et al, 1982Inan et al, , 1984Inan et al, , 1985Dowden, 1985), and particle precipitation (Koons et al, 1981;Vampola, 1987Vampola, , 1990. Moreover, magnetospheric amplification of VLF pulses through wave-electron interaction is enhanced during magnetic storms (Smith and Clilverd, 1991).…”
mentioning
confidence: 99%
“…Observations of nearly mono-energetic-electron ,beams in the drift loss cone within this region by Vampola, Koons, Imhof, Datlowe, and coworkers [Vampola, 1977[Vampola, , 1987Koons et al, 1981;Imhof et al, 1983Imhof et al, , 1989Imhof, 1990, 1993] have been interpreted in terms of pitch-angle scattering caused by cyclotron-reSonant interactions of trapped electrons with waves from ground-based VLF transmitters. These waves propagate within the plasmasphere in the Whistler mode.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…A complete ion and electron spectrum was taken every second and a complete angular distribution was obtained in one spin period (20 s). We also use data from a solid state detector telescope which measured energetic ions (described by Lyons et al [1987]) and a magnetic focusing spectrometer which measured energetic electrons (described by Vampola [1987]; Vampola and Adams [1987]). From these detectors, we use the two lowest energy ion channels (integral flux of > 80 and > 165 keV protons) and the two electron energy channels with the best sensitivity (centered at 33 keV and 235 keV).…”
Section: Methodsmentioning
confidence: 99%